All‐systolic non–ECG‐gated myocardial perfusion MRI: Feasibility of multi‐slice continuous first‐pass imaging. Issue 6 (6th June 2015) - Sharif, Behzad; Arsanjani, Reza; Dharmakumar, Rohan; Bairey Merz, C. Noel; Berman, Daniel S.; Li, Debiao
Abstract : Purpose: To develop and test the feasibility of a new method for non–ECG‐gated first‐pass perfusion (FPP) cardiac MR capable of imaging multiple short‐axis slices at the same systolic cardiac phase. Methods: A magnetization‐driven pulse sequence was developed for non–ECG‐gated FPP imaging without saturation‐recovery preparation using continuous slice‐interleaved radial sampling. The image reconstruction method, dubbed TRACE, used self‐gating based on reconstruction of a real‐time image‐based navigator combined with reference‐constrained compressed sensing. Data from ischemic animal studies (n = 5) was used in a simulation framework to evaluate temporal fidelity. Healthy subjects (n = 5) were studied using both the proposed approach and the conventional method to compare the myocardial contrast‐to‐noise ratio (CNR). Patients (n = 2) underwent adenosine stress studies using the proposed method. Results: Temporal fidelity of the developed method was shown to be sufficient at high heart‐rates. The healthy volunteers studies demonstrated normal perfusion and no dark‐rim artifacts. Compared with the conventional scheme, myocardial CNR for the proposed method was slightly higher (8.6 ± 0.6 versus 8.0 ± 0.7). Patient studies showed stress‐induced perfusion defects consistent with invasive angiography. Conclusion: The presented methods and results demonstrate feasibility of the proposed approach for high‐resolution non–ECG‐gated FPP imaging of 3 myocardial slices at the same systolic phase, and indicate its potential for achieving desirable image quality (high CNR and no dark‐rim artifacts). Magn Reson Med 74:1661–1674, 2015. © 2015 Wiley Periodicals, Inc.